Advanced 2D Materials for Emerging Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
The properties of materials are significantly dependent on not only their composition, crystal phase, and facets, but also their dimensionality. Normally, three dimensions (0D, 1D, and 2D) of materials are defined and reported. Specially, 2D materials are anticipated to be serious contenders for high-volume semiconductor manufacturing within the next decade. The typical applications of 2D material cover catalysis, energy conversion and storage, photonics, optics, electronic devices, and diagnostics. This Special Issue of Nanomaterials, entitled “Advanced 2D Materials for Emerging Applications”, seeks to present state-of-the-art research statues and advances in this rapidly evolving area. Contributions are on topics covering the general principles and applications of 2D materials in a wide range of devices, including supercapacitor, reconfigurable electronics, zinc-ion battery, radiofrequency device.